Pengaruh Customer Centric Dan Religious Framing Terhadap Keputusan Pembelian: customer centric : religious framing : keputusan pembelian - putra, gilang kharisma; Astuti, Fitria Yuni (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2023)
This study aims to examine the effect of customer centricity and religious framing on purchasing decisions with the Hajah Subagyo restaurant as the research sample, the Hajah Subagyo restaurant was chosen because it represents the Islamic name in the business name, namely